(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The present study aimed to investigate the effect of re-operations engineering business in continuous improvement, as the rapid development of service activities generally private and the great diversity in the goals of its operations and programs of the university and the service has led to the increasing importance of re-operations engineering business as well as continuous improvement so began to study the relationship between the re engineering and continuous improvement of university service, and applied study on a sample of professors from the faculties of administration, economics and law. Find and reach to several conclusions, notably that the preparation of the teaching staff training sessions on how to use modern teaching techniques and methods of teaching as well as the stomach sessions for employees will help to achieve the main goal, which is the capacity of self-development for teachers and staff the most important.